Problems in Transition to a Digital Library: An Indian Perspective - Jeevan, V.K.J.; Dhawan, S.M. (DESIDOC Journal of Library & Information Technology, 2003)
This paper highlights the problems and issues in the transition to a digital library environment. The problems and issues relate to integration of information technologies in libraries and information centres, in particular to relevant aspects such as IT infrastructure planning, digital library tools and software, models for resource development, IT training needs, resource development, content development, and copyright management, etc. The paper also reflects on the changing roles of the libraries and librarians in the context of emerging digital library environment. http://dx.doi.org/10.14429/dbit.22.6.3578